POLA PERSEBARAN NITRAT DAN PHOSPHAT DENGAN MODEL AQUATOX2.2 SERTA HUBUNGAN TERHADAP TANAMAN ENCENG GONDOK PADA PERMUKAAN DANAU (STUDI KASUS DANAU RAWA PENING KABUPATEN SEMARANG) - Budihardjo, Mochamad Arief; Huboyo, Haryono Setiyo (Universitas Diponegoro, 2007)
Rawa Pening meets with environment degradation like other lakes in Indonesia which is caused by pollutant from the outside especially nitrate and phosphate. Degradation that is happened in this time is water hyacinth blooms (enceng gondok) on the surface of the lake. This makes Rawa Pening’s function become annoyed such as PLTA, tourism, fishery, and irrigation. This degradation keeps going and tends to increase so that it is necessary to do nitrate and phosphate monitoring for next time. The taking of sample has done at three points: upstream (S1), middle (S2), and downstream (S3) which are used as an observed data. Method used research is predicting nitrate and phosphate concentration for ten years later by Aquatox 2.2. Model validation done with compare observed result and model result. Mean error from this validation less than 5% so that the model supposed describe the field conditions. Simulation model result that obtained for ten years later are nitrate 0,037 mg/L (S1); 0,035 mg/L (S2); 0,032 mg/L (S3) and phosphate 0,296 mg/L (S1); 0,274 mg/L (S2); 0,262 mg/L (S3). Dispersion pattern of simulation model result made by dividing lake into three segment, then search current velocity to get dispersion distance. This pattern showed that nitrate and phosphate concentration progressively decline from S1 to S3. Based on this pattern is knowable enceng gondok amount estimation also progressively decline from S1 to S3. The calculation sum of enceng gondok estimation in upstream is about 66 plants and in downstream is about 43 plants. The width of enceng gondok progressively decline according to the amount of enceng gondok in every contour. But the density of enceng gondok not decline because the differences of every contour area. Support energy of Rawa Pening surface area to enceng gondok is about 180.594,59 m² and support energy of the enceng gondok’s total is about 14.054 plants. Wet longitudinal section daily loads of Rawa Pening is about 6.319.405,41 m².